How big is a beaked whale? A review of body length and sexual size dimorphism in the family Ziphiidae - MacLeod , Colin D. (J. Cetacean Res. Manage., 2023)
There is a paucity of data on the family Ziphiidae (the beaked whales) and even basic information, such as body length, is not available for some species. This review examines published records of body length for 20 of the 21 currently recognised species of beaked whale. It considers maximum, median and modal body lengths, where possible by sex. For Cuvier’s, Blainville’s and Gray’s beaked whales, modal and median lengths were much shorter than the maximum reported lengths; this may reflect misidentification of the largest animals. Although males of some species reached a greater maximum size, there was only a significant difference in median body length for three species: True’s beaked whale; the strap-toothed whale; and Gervais’ beaked whale. In all three cases, females had a significantly larger median length. The apparent lack of consistent sexual dimorphism in body length suggests that, while male beaked whales use their tusks as weapons to compete aggressively for access to receptive females, large size does not give a competitive advantage. This may be a result of the way the sexually dimorphic tusks are used during combat. The only exception to this rule appears to be the northern bottlenose whale, for which males consistently reach greater body lengths than the largest females. Male-male combat appears to take a different form in this species.